2007
DOI: 10.1097/mph.0b013e318157fdac
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Role of Coping and Family Functioning in Health Outcomes for Adolescents With Sickle Cell Disease

Abstract: Risk-and-resistance models identify factors that predict psychosocial adjustment to pediatric chronic illness, including sickle cell disease (SCD), but have not been applied to understand health outcomes. The study objectives were to examine prospectively the relationship of coping and family functioning with health outcomes for adolescents with SCD, accounting for sociodemographic and psychosocial risk. Forty-one adolescents and their families (41 primary caregivers, 9 second caregivers, and 15 healthy siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 39 publications
3
51
0
Order By: Relevance
“…18,19 Research has shown that stress is significantly related to poor psychological adjustment on the part of the parents to the increased demands of children with SCD, including frequent pain and frequent use of both routine and urgent healthcare services, as well as realisation of the short life expectancy of their child. 18,20 A study conducted in Nigeria found that children with SCD reported more frequent absences from school and poorer academic achievement compared to their healthy siblings. 21 Parents of children with SCD have shown increased SCD knowledge compared to parents of children without SCD; moreover, the absence of family discussion about SCD was associated with lower knowledge levels and awareness of SCD and the value of PMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Research has shown that stress is significantly related to poor psychological adjustment on the part of the parents to the increased demands of children with SCD, including frequent pain and frequent use of both routine and urgent healthcare services, as well as realisation of the short life expectancy of their child. 18,20 A study conducted in Nigeria found that children with SCD reported more frequent absences from school and poorer academic achievement compared to their healthy siblings. 21 Parents of children with SCD have shown increased SCD knowledge compared to parents of children without SCD; moreover, the absence of family discussion about SCD was associated with lower knowledge levels and awareness of SCD and the value of PMS.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 Certain beliefs reported by the majority of participants in the current study-that SCD is serious, that it is frightening to have an SCD-affected child, that the disease can have an impact on school performance and that having a child with SCD can affect the parents' personal lives-are supported by findings from other studies in the literature. [18][19][20][21] Parents of children with chronic illnesses such as SCD have reported significantly greater stress than the parents of healthy children. 18,19 Research has shown that stress is significantly related to poor psychological adjustment on the part of the parents to the increased demands of children with SCD, including frequent pain and frequent use of both routine and urgent healthcare services, as well as realisation of the short life expectancy of their child.…”
Section: Discussionmentioning
confidence: 99%
“…Such parenting capacity variables include, among others, parenting stress, perceived child vulnerability, and parental overprotection. Parenting stress is conceptualized as parents' perceptions of stress in various areas, including parent-child interactions, difficult child characteristics, and parents' individual characteristics (Abidin, 1990); and has been associated with more internalizing and externalizing problems (Colletti et al, 2008), medical nonadherence (Fredericks, Lopez, Magee, Sheick, & Opipari-Arrigan, 2007), and greater illness severity and health care utilization (Barakat et al, 2007). Parental overprotection has been defined as overanxious parenting in which the parent displays excessive protective behaviors given the child's developmental stage (Thomasgard & Metz, 1999).…”
mentioning
confidence: 99%
“…However, earlier studies from our center have documented a broad range of socioeconomic status and education, slightly skewed toward lower income. 29 In addition, earlier reports of low "numeracy" indicated that Americans of most socioeconomic groups have difficulty with abstract numerical representations of quantitative information.…”
Section: Discussionmentioning
confidence: 98%
“…Active clinical research programs in SCD are exploring new pharmacologic agents, gene therapy, and stem cell transplantation from unrelated donors. 3,29,30 In each study of a new treatment, risk-benefit information for the new treatment is likely to be compared with the risk-benefit information for hydroxyurea as a standard-care option. [31][32][33][34][35][36] The findings of this study may be helpful in introducing visual methods to augment communication of quantitative risk information to families.…”
Section: Discussionmentioning
confidence: 99%